Pharmacological potential of endocannabinoid and endocannabinoid-like compounds in protecting intestinal structure and metabolism under high-fat conditions - Vari, Francesco; Serra, Ilaria; Friuli, Marzia; Cavallo, Viviana; Gammaldi, Nicola; Vergara, Daniele; Salzet, Michel; Giudetti, Anna M. (Frontiers in Pharmacology, 2025)
The intestine plays a crucial role in nutrient absorption, digestion, and regulation of metabolic processes. Intestinal structure and functions are influenced by several factors, with dietary composition being one of the most significant. Diets rich in various types of fats, including saturated, monounsaturated, and polyunsaturated fats, have distinct effects on intestinal cell metabolism and overall intestinal health. High consumption of saturated fats, frequently found in animal products, has been associated with inflammation, altered gut microbiota composition, and impaired intestinal barrier function, with potential consequences such as metabolic disorders, obesity, and insulin resistance. In contrast, monounsaturated fats, found in foods such as olive oil and avocado, promote intestinal cell integrity, reducing inflammation and supporting a healthier microbiome. Polyunsaturated fatty acids, especially omega-3 fatty acids, have shown anti-inflammatory effects and may improve the function and adaptability of intestinal cells, promoting better nutrient absorption and immune regulation. Recent evidence suggests that endocannabinoids and endocannabinoid-like compounds, such as oleoylethanolamide have a protective effect on the function and structure of the intestine. These endocannabinoid pathways modulating compounds can act on receptors in the intestinal epithelium, improving the intestinal barrier and counteracting inflammation, facilitating a more favorable environment for intestinal health. Understanding how different fats influence intestinal metabolism and the protective role of endocannabinoids and endocannabinoid-like compounds is essential to developing dietary strategies to improve intestinal health and prevent diet-related diseases. This review explores the impact of high fats on intestinal metabolism and the main role of endocannabinoids and endocannabinoid-like compounds on these effects.